Prevalence, clinical features and factors associated with psychosis among Idiopathic Parkinson’s Disease (IPD) patients in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) - Md Rosli, Najwa Hanim; Abdul Rahman, Abdul Hamid; Mohamed Ibrahim, Norlinah (IIUM Medical Journal Malaysia, 2016)
Introduction: This was a cross sectional study of the prevalence of psychosis and its characteristic in patients with Idiopathic PD (IPD) attending the neurology clinic, Pusat Perubatan Universiti Kebangsaan Malaysia (PPUKM). Methods: The assessment was using a structured demographic data and clinical information questionnaire, Mini-International Neuropsychiatric Interview (MINI) 6.0.0, Starkstein’s Apathy Scale (AS), Mini Mental State Examination (MMSE), Movement Disorder Society – Unified Parkinson Disease Rating Scale (MDS-UPDRS) Q1-Q6, Hoehn and Yahr (H&Y) stages of PD and Schwab and England Activities of Daily Living (ADL) scale. Results: 112 patients were studied. Psychosis was identified in 39 (34.8 %) patients (33 patients with hallucination only, 6 with hallucination and delusion (psychotic disorder) and none with delusions only). Among patients experiencing hallucinations, 14 (35.9%) had a visual hallucination only, 12 (30.8%) had auditory hallucinations only, and 13 (33.3%) had both visual and auditory hallucinations. Psychosis were more common in IPD patients with cognitive impairment using MDSQ1 scoring (OR 0.15; 95% CI, 0.05-0.63; P = p‹0.05) while others variables were not significant. The analysis, among patients with psychotic symptoms only and patients with psychotic disorder showed education level (p<0.05), duration of illness (OR 1.8; 95% CI, (-10.7 - -3.5; p <0.01), cognitive impairment score - MDSQ1 (OR 0.2; 95% CI, 0.2-0.9; p<0.01), H&Y score (OR 0.4; 95% CI, -2.1- -0.6; p<0.01) and ADL score (OR 0.6; 95% CI, 0.3 – 2.6; p<0.05) were significant. Conclusions: Lower education level, longer duration of illness, more advance stage of Parkinson disease and less functioning in ADL were significant in psychotic disorder in IPD.